2002
DOI: 10.1038/sj....bjc.6600169...
|View full text |Cite
|
Sign up to set email alerts
|

Isolated limb perfusion with actinomycin D and TNF-alpha results in improved tumour response in soft-tissue sarcoma-bearing rats but is accompanied by severe local toxicity

Abstract: Previously we demonstrated that addition of Tumour Necrosis Factor-a to melphalan or doxorubicin in a so-called isolated limb perfusion results in synergistic antitumour responses of sarcomas in both animal models and patients. Yet, 20 to 30% of the treated tumours do not respond. Therefore agents that synergise with tumour necrosis factor alpha must be investigated. Actinomycin D is used in combination with melphalan in isolated limb perfusion in the treatment of patients with melanoma in-transit metastases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…This data was not confirmed by other studies that reported a direct cytotoxic effect of TNF- α on tumoral cell [125], an indirect action on tumor vessels [126] and a synergic action with conventional antineoplastic agents [127, 128]. …”
Section: Resultscontrasting
confidence: 83%
“…This data was not confirmed by other studies that reported a direct cytotoxic effect of TNF- α on tumoral cell [125], an indirect action on tumor vessels [126] and a synergic action with conventional antineoplastic agents [127, 128]. …”
Section: Resultscontrasting
confidence: 83%
“…In rat sarcoma ILP models, doxorubicin augmented rTNF-alpha activity, but less so than the augmentation observed with rTNF-alpha and melphalan [136,137]. Actinomycin D and rTNF-alpha were combined and found to have potent antitumor activity in a rat sarcoma ILP model; however severe toxicity including destruction of the regional muscle tissue and edema was observed [138]. A consistent theme of these studies was the idea that rTNF-alpha increased the exposure of the tumor cells to the chemotherapeutics by altering vascular permeability.…”
Section: Efficacy In Pre-clinical Models and Clinical Trialsmentioning
confidence: 93%
“…Conversely, in several animal and human models of systemic [62] and/or locoregional cancer treatment the combination of TNF with conventional antineoplastic agents (e.g. melphalan, doxorubicin, paclitaxel, actinomycin-D, cisplatin) strikingly increases the tumor response rates [55][56][57][58][59]63]. The mechanism of this anticancer synergism has been the object of some hypotheses.…”
Section: Synergism With Conventional Antineoplastic Agentsmentioning
confidence: 96%
“…Despite the antitumor effects illustrated above, TNF alone is only marginally active in inducing tumor regression in some in vivo animal models (using both autologous and xenogeneic/human tumors) [55][56][57][58][59] and most importantly in humans, even when high doses are given through locoregional drug-delivery systems [2,60,61]. Conversely, in several animal and human models of systemic [62] and/or locoregional cancer treatment the combination of TNF with conventional antineoplastic agents (e.g.…”
Section: Synergism With Conventional Antineoplastic Agentsmentioning
confidence: 97%